The Arts and Biocultural Diversity: Further Ideas - Diane Butler (TAMA: Journal of Visual Arts, 2025)
The invitation to come to Universitas Sebelas Maret in Surakarta, Central Java to give a talk for a very important 1st Conference on Visual Art, Design, and Social Humanities (CONVASH), convened by the Faculty of Fine Arts and Design on 2 November 2019, offered an opportunity to return to a subject that I believe is central for addressing nearly all issues which challenge us now and will in the future: biocultural diversity. In 2017, for the International Conference on Biodiversity convened in Bali by Masyarakat Biodiversitas Indonesia and Universitas Sebelas Maret, Surakarta, I urged scientists to work with artists so that the arts can be more sufficiently acknowledged, documented and explained in terms of the connections between cultural and biological diversity. The present paper puts forth further ideas about how artists can work with scientists to develop interdisciplinary practice-based methods for enhancing beneficial human-nature relationships. Keywords: arts, biocultural diversity, cultural creativity, practice-based methods, tangible and intangible cultural heritage